New species and records of the genus Geodromicus Redtenbacher, 1857 (Coleoptera: Staphylinidae: Omaliinae) from Taiwan - Shavrin, Alexey V.; Smetana, Aleš (Zootaxa, 2016)
Two new species of the genus Geodromicus Redtenbacher, 1857 from Taiwan are described and illustrated: G. philydroides sp. n. (Nantou Hsien) and G. taiwanensis sp. n. (Kaohsiung Hsien, Hualien Hsien). Additional material and a new synonymy for G. ohkurai (Hayashi, 1992) = G. ohkurai yushanensis (Hayashi, 1992), syn. nov. are proposed. A key to species known from Taiwan is given.